2010
DOI: 10.1155/2010/873167
|View full text |Cite
|
Sign up to set email alerts
|

Poor Accuracy of Methods Currently Used to Determine Umbilical Catheter Insertion Length

Abstract: This study compares the methods of Dunn and Shukla in determining the appropriate insertion length of umbilical catheters. In July 2007, we changed our policy for umbilical catheter insertions from the method of Dunn to the method of Shukla. We report our percentage of inaccurate placement of umbilical-vein catheters (UVCs) and umbilical-artery catheters (UACs) before and after the change of policy. In the Dunn-group, 41% (28/69) of UVCs were placed directly in the correct position against 24% (20/84) in the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 21 publications
4
34
1
4
Order By: Relevance
“…In the study by Verheij et al 8 where they considered T1-T11 as the correct site of insertion for the umbilical arterial catheter found that by Dunn's formula 6 the accuracy of insertion was 63% and using Shukla's formula 7 the accuracy was significantly (P<0.05) better at 87%. In spite of taking the normal from T1, the catheters were over inserted in rest of the children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Verheij et al 8 where they considered T1-T11 as the correct site of insertion for the umbilical arterial catheter found that by Dunn's formula 6 the accuracy of insertion was 63% and using Shukla's formula 7 the accuracy was significantly (P<0.05) better at 87%. In spite of taking the normal from T1, the catheters were over inserted in rest of the children.…”
Section: Discussionmentioning
confidence: 99%
“…8 The need for a simple and reliable common formula to predict the length of the catheter to be inserted in preterm and term babies is lacking. In the study by Wright et al 3 only <1500 g babies were included in the study and the study group was 74 neonates as compared with our study where 26 (26.3%) were term and the rest (n ¼ 73) were preterm (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The most appropriate position for an umbilical venous catheter tip position is considered as the junction of the inferior vena cava and right atrium (6,7,(9)(10)(11). This regions corresponds to the T9-10 range on anterior-posterior chest radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…The position of placement of the catheters, which proceeded along the vertebral column and were specified with anterior-posterior chest radiograph, was considered appropriate when it was between the 9th and 10th thoracic vertebrae (T9-10), "too high" when it was above T9 and "too low" when it was below T10 (6,7). Catheters that directed to the portal or splenic veins were defined as having an abnormal position.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation